Human resource management and industrial relations - Khan, Abdul Awal; M. A. Taher (Dhaka : Abir Publication, 2009)
Business
Keywords: Human Resouce Management; Industrial relations; Human resource policy; Planning; Job analysis; Training and development; Evaluation; Motivation; Discipline